Improving Student PAI Learning Outcomes with the Inquiry Method in Class IV SDN 05 Pauh Sub-District Lubuk Sikaping Pasaman District - Elfianis (BiCED Proceeding, 2024)
This study aims to improve students' learning outcomes in writing Quranic verses through the application of task-based and collaborative learning models in grade IV of SDN 08 Kubu Tanjung. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection activities. The results show that this learning model is effective in enhancing cooperation among students, motivation to learn, and students' learning outcomes. In Cycle I, some students faced difficulties in collaborating, but in Cycle II, there was a significant improvement in cooperation, task completion, and understanding of the material. The average class score reached 87.3, indicating that this learning approach successfully improved students' skills in writing Quranic verses. This study concludes that the task-based and collaborative approach can effectively improve students' learning outcomes, especially in writing Quranic verses.